2018
DOI: 10.1016/j.aninu.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Potential antioxidant bioactive peptides from camel milk proteins

Abstract: Camel milk is traditionally considered to have medicinal characteristics that it has potential health benefits and could help to treat several illnesses. Particularly, it is closest to human breast milk and has high levels of nutrients and bioactive components. The aim of this study was to explore the antioxidant peptides derived from protein fractions of camel milk. Camel milk proteins (CMP) were fractionated into camel casein protein (CCP) and camel whey protein (CWP), which were hydrolyzed with pepsin to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 46 publications
4
52
0
1
Order By: Relevance
“…Antioxidants are known to scavenge free radicals, and therefore considered strong candidates for development of radioprotector [16]. The antioxidant capacities of bioactive peptides, in which different amino acid compositions have different validities, have been extensively studied [8,17,18]. Previous studies demonstrated that walnut protein hydrolysate was an effective antioxidant for scavenging various free radicals through different scavenging ways and make it a potential therapeutic agent for alleviation of memory impairment [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants are known to scavenge free radicals, and therefore considered strong candidates for development of radioprotector [16]. The antioxidant capacities of bioactive peptides, in which different amino acid compositions have different validities, have been extensively studied [8,17,18]. Previous studies demonstrated that walnut protein hydrolysate was an effective antioxidant for scavenging various free radicals through different scavenging ways and make it a potential therapeutic agent for alleviation of memory impairment [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the literature. Recently, Ibrahim et al (2018) studied potential antioxidant bioactive proteins from CM proteins. Reversed-phase HPLC was used for the fractionation of peptides.…”
Section: Lipid Peroxidation Measurement and Thiol Group Determinationmentioning
confidence: 99%
“…On the other hand, the lactophorin-derived peptides, R 75 RHQNQNPK 83 and R 76 HQNQNPK 83 , found in this study were embedded in the middle part of mature lactophorin. Ibrahim et al [38] recently found two lactophorin-derived peptides, E 113 NTMRETMDFLKSLF 127 and A 79 TTLEGKLVEL 89 , in pepsin-digested camel milk whey hydrolysates that confer tolerance against H 2 O 2 -induced oxidative stress to yeast cells. The biological significance of the lactophorin-derived peptides found in the fermented camel's milk in this study remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%